Relocation of Moderate-to-small Earthquakes in and Around Hainan Island - Yunfei GUO; Jianshe LEI; Penghu GUAN (CT Lilun yu yingyong yanjiu)
In this study, 6090 P-wave and 5545 S-wave arrival time data recorded by 68 seismic stations during 415 seismic events in and around Hainan Island between November 18, 2008, and October 26, 2023, were collected from the China Earthquake Networks Center observational bulletins. The double-difference algorithm was used for relocation, and eventually, the high-quality source parameters of 313 earthquakes were obtained. Our results show that the average location errors of earthquakes in the E-W, N-S, and vertical directions are 0.14, 0.15, and 0.22 km, respectively. The earthquakes are concentrated mainly in the northeastern and southwestern Hainan Island, with the dominant depths being 5~15 km. In the northeastern Hainan Island, the earthquakes present predominantly an NNE-SSW banded distribution, which is not consistent with the NW-SE Puqian-Qinglan, Haikou-Yunlong, and Changliu-Xiangou Faults. Since the 2019 Sanya M 4.2 earthquake, a series of moderate-to-small seismic swarms have been developed in southwestern Hainan Island. The earthquakes occurred predominantly near the Jiusuo-Lingshui Fault and west of the Ledong-Tiandu Fault. This suggests that the occurrence of earthquakes may be related to fault activity. Combined with the findings of previous studies, the spatiotemporal seismic changes in southwestern Hainan Island suggest that the 2019 Sanya M4.2 earthquake likely promoted the formation of the Ledong seismic swarm. The occurrence of earthquakes in and around Hainan Island is jointly affected by fault zone activity, volcanic activity, and fluid action.